(untitled) (International Journal of Mathematics and Physics, 2023)
Total electron content measurements by using dual-frequency signals of global navigation satellite systems (GNSS) makes it possible to obtain the global distribution of electron density of ionosphere with high spatial and temporal resolution. Such high spatial and temporal resolution allows to explore of small-scale traveling ionospheric disturbances generated by terrestrial geophysical events, including seismic activity, solar terminator passage, and atmospheric cyclones. One of the features of measuring the total electron content of the ionosphere with GNSS is that the measurements are made at the line of intersection of the satellite-receiver beam with the layer of maximum ionization of the ionosphere at height of ≈ 300 km. At the same time, due to the orbital motion of the satellites and the Earth rotation, the ionospheric points at which the measurements are providing carrying out a movement relative to each other, relative to the Earth and relative to the traveling ionospheric disturbances. Such a relative motion of the measurement points causes the occurrence of the Doppler effect and leads to a distortion of the wave parameters of the total electron content variations. In particular, the determination of the period of traveling ionospheric wave disturbances on the basis of time series leads to large distortions depending on the used satellite, the time and coordinates of the receiver. This paper describes a method for determining the exact wave parameters –frequency, wavelength, and propagation velocity of traveling ionospheric wave disturbances, based on the use of godochrones to analyze TEC variations. The difference between the wave parameters measured by the proposed method and from the time series of TEC data is shown on an example of wave disturbances generated by the passage of solar terminator.